Digestibilidade de alimentos e fontes lipídicas para juvenis de Pacamã Lophiosilurus alexandri - Karen Daianny Macedo Melo (2015)
The pacamã (Lophiosilurus alexandri) is a native fish of the San Francisco River that has aroused the interest of researchers because presents favorable characteristics for its captive breeding. The first study aimed to determine the coefficient of apparent digestibility (CAD) of dry matter, protein and energy for fish meal, meat and bone meal, soybean meal, wheat bran, roasted whole soybean and corn gluten meal for pacamã juveniles (L. alexandri). Two reference diets were used: practical diet and purified diet. CDA have significant interaction (P <0.05) between foods and diets reference. The interference of the reference diet in CADCP was observed for fish meal, meat and bone meal and wheat bran, where the purified reference diet provided higher rates. In practice CADDM diet promoted a higher result for roasted whole soybean and again the wheat bran. For CADGE only the soybean meal diets presented influence of the reference, where higher value was obtained in purified diet similar to CADCP. As the evaluation of food, the lowest CADDM and CADGE was observed in soybean meal, while the greatest results were presented at the fish meal, meat and bone meal and corn gluten meal. Purified diet that conclusion promoted greater CADCP and CADGE the assessed food and pacamã juveniles showed good use of protein foods of plant origin. In the second study, the objective was to evaluate the use of four lipid sources: fish oil, soybean oil, canola oil and corn oil on performance, muscle composition, fatty acid composition, hematological index and liver morphology juveniles of pacamã (L. alexandri). Different lipid sources do not affect fish performance, and did not affect the nutritional composition of muscle and liver (P> 0.05) except for the fatty acid profile. The lipid profile reflected in the muscle of the diets was observed and an increase in EPA and DHA content in the muscles of pacamãs fed with lipid sources of vegetable origin. Since the liver, fatty acids did not reflect some of the diets, the result observed for saturated fatty acids and linoleic fatty acid (C18: 2 n-6). The total protein and hematocrit were not affected by the composition of lipid sources, while triglycerides and total cholesterol had higher plasma concentration of pacamãs fed fish oil. HDL lipoproteins, LDL and VLDL remained unchanged as well as the hepatic parenchyma did not show increased pacamãs of hepatocytes. It follows that the sources of fat, fish oil, soybean oil, corn oil and canola oil can be supplied to juvenile pacamã. Providing adequate performance, higher fatty acids EPA and DHA in the musculature, without causing alterations in liver cells. However, fish oil increases the levels of triglycerides and cholesterol circulating in this species.